State maneuver in the capitalist world-economy: A political geography of contextualized agency. (November 2018) - Flint, Colin; Dezzani, Raymond
The purpose of this paper is to elucidate a theoretical perspective and outline an analytical framework for state maneuver in the hierarchical world-economy that incorporates the idea of context with structural imperatives. Maneuver is the agency of states within conjunctures of structural imperatives and spatial settings of inter-state alliances and established cultural understandings and historic relations. The hierarchy of the capitalist world-economy is conceptualized as an emergent structure, one that emerges from competition for scarce resources. The resources are economic attributes defined by the process of capital accumulation, political attributes emanating from the imperative of state territorialization, and the agglomeration of these attributes in spatial formations. The structure is emergent from the actions of states that create these spatial formations, but transformation is limited given structural constraints. States maneuver can be modeled as Markov transition probabilities decomposable as logits for covariate analysis.